The Effect of Knowledge and Promotion on Customer Interest in Using Services PT. Pegadaian Branch, Parepare City - Asriani, Asriani (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
This study aims to determine: The influence of customer knowledge on customer interest in using PT Pegadaian services at the Parepare city branch and to determine the influence of promotion on customer interest in using PT Pegadaian services, both of which greatly influence customer interest. The method used is quantitative and data is obtained by means of questionnaires, interviews and documentation. Data analysis techniques: validity test, reliability test, statistical test and classical assumption test. The results of the study indicate that the influence of customer knowledge partially has a significant effect on customer interest in using PT Pegadaian services and then promotion partially has a significant effect on customer interest in using PT Pegadaian services.